Solve the following pair of linear equations by the substitution method

3x – y = 3

9x – 3y = 9

Advertisement Remove all ads

#### Solution

3x - y = 3 (1)

9x - 3y = 9 (2)

From (1), we obtain

y = 3x - 3 (3)

Substituting this value in equation (2), we obtain

9x - 3(3x - 3) = 9

9x - 9x + 9 = 9

9 = 9

This is always true.

Hence, the given pair of equations has infinite possible solutions and the relation between these variables can be given by y = 3x - 3

Therefore, one of its possible solutions is x = 1, y = 0.

Concept: Algebraic Methods of Solving a Pair of Linear Equations - Substitution Method

Is there an error in this question or solution?

#### APPEARS IN

Advertisement Remove all ads